2013
DOI: 10.1111/jch.12200
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Treatment of Resistant Hypertension: The Critical Role of Ambulatory Blood Pressure Monitoring

Abstract: Hypertension is an illness that generally requires lifelong treatment with blood pressure (BP)-lowering drugs. It is, therefore, understandable that increasing attention is being paid to interventional procedures that might provide a "cure" for hypertension and obviate the need for costly therapy that is not always without unwanted effects. Such interventional techniques are confined, for the moment, to patients with drug-resistant hypertension, ie, BP levels above a specified target despite adherence to at le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…Because hypertension is generally an asymptomatic condition that requires lifelong treatment with medication, interest has grown in recent years in interventional and device‐based procedures as alternative treatments . The most researched of such techniques has been catheter‐based renal denervation (RDN), an invasive procedure that involves radiofrequency ablation of the sympathetic nerves surrounding the renal arteries .…”
mentioning
confidence: 99%
“…Because hypertension is generally an asymptomatic condition that requires lifelong treatment with medication, interest has grown in recent years in interventional and device‐based procedures as alternative treatments . The most researched of such techniques has been catheter‐based renal denervation (RDN), an invasive procedure that involves radiofrequency ablation of the sympathetic nerves surrounding the renal arteries .…”
mentioning
confidence: 99%
“…A subsequent position statement of the American Heart Association (AHA) considered patients whose BP is controlled by ≥4 antihypertensive medications to be also resistant to treatment (controlled resistant hypertension) [11]. More recently, it has been suggested that a time frame of at least 3 months of effective treatment should be included in the definition of resistant hypertension [24,25]. Although resistant hypertension by definition is considered not controlled, it should not be used identically with the term Buncontrolled hypertension^which refers to all hypertensive patients without adequate BP control under treatment [12••].…”
Section: Definition Of Resistant Hypertensionmentioning
confidence: 99%
“…Second, it is important to determine more rigorously whether RDN is efficacious alone, and, if so, whether it is helpful as an adjunctive therapy for patients receiving antihypertensive medications. Third, ABPM is an important methodology . Fourth, assessment of long‐term safety is required.…”
Section: Encouraging Fundamental Agreements With Another Publicationmentioning
confidence: 99%